Vol. 102 : Space Engineering: V International Forum for Young Scientists, April 18-20, 2017, Tomsk, Russia; [proceedings]; MATEC Web of Conferences - Borikov V. N. Valery Nikolaevich; Uchaykin (Uchaikin) S. V. Sergey Victorovich; Baranov P. F. Pavel Fedorovich; Ivanova V. S. Veronika Sergeevna; Dolgikh A. G. Antonina Gennadievna; Ignatovskaya A. A. Anastasiya Albertovna (2017, 2017)
Title screen